EVALUASI MANAJEMEN PENGUNJUNG STUDI KASUS TAMAN WISATA CANDI PRAMBANAN - , YESSY SUPANDI, S.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prambanan Temple Compounds is a world heritage site used for tourism. The use of Prambanan Temple Compound for tourism causes an increase in the number of visitors both from within and outside the country. Visitors with various behavior prompted the government to form a state-owned company, that is PT. Taman Wisata Candi Borobudur, Prambanan dan Ratu Boko (PT. TWCBPRB) that focuses on the use of the cultural heritage based on preservation. PT. TWCBPRB as the manager of tourism is responsible for managing tourism activities in zone 2 of Prambanan Temple Compounds in order not to jeopardize cultural heritage site which is located in zone 1. One of strategies deals with visitors is visitor management. Visitor management must be executed to maintain the state of universal values owned by Prambanan Temple Compounds as a world heritage site. This study aimed to evaluate the implementation of visitor management by PT. TWCBPRB. Evaluation needs to be carried out to produce references that can be used in subsequent management. The research was conducted by field observation, interviews, and literature study. The finding generated in this study is that in general the PT. TWCBPRB is not entirely in favor of the preservation of the Prambanan Temple Compound. Evaluation of management involving stakeholders which have interests of the existence of Prambanan Temple Compound has never been held, besides, the visitor management has not been done optimally as well. Several ways which can be conducted to take advantage of Prambanan Temple Compound to improve tourism service in Prambanan Temple Compound based on preservation are by holding regular meetings among stakeholders for coordination and evaluation, and implementing visitor management optimally